MODERN VIEWS ON PREVENTION AND TREATMENT OF VENTRICULAR TACHYCARDIA, PATHOGENESIS - Burhonova Nigora Shodiyev Xumoyun Raxmonov Azamat Komilova Moxinur (Journal of Science in Medicine and Life, 2024)
Ventricular tachycardia 3 consecutive ventricular complexes with a frequency of 120 beats per minute. Depending on the duration of symptoms, they can range from no symptoms to palpitations, hemodynamic collapse, and death. Diagnosed by electrocardiography. Prolonged episodes are treated with cardioversion or antiarrhythmics depending on the symptoms. If necessary, long-term treatment is carried out using an implantable cardioverter defibrillator. Some experts use a rate ≥ 100 beats per minute to test for ventricular tachycardia (VT). Ventricular rhythms that repeat at a lower rate are called accelerated idioventricular rhythms, or slow VT; as a rule, they are comfortable and do not require treatment if patients do not have clinical symptoms. Most patients with VT have significant heart disease, particularly prior myocardial infarction or cardiomyopathy. Disorders of electrolyte metabolism (especially hypokalemia and hypomagnesemia), acidemia, hypoxemia, and side effects of drugs contribute to VT. Long QT syndrome (congenital or acquired) is associated with a special form of VT, torsade de pointes (TdP).